1996
DOI: 10.1212/wnl.46.6.1534
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic medication and oral contraceptive interactions

Abstract: Hepatic enzyme-inducing antiepileptic drugs (AEDs) lower oral contraceptive (OC) sex hormone levels approximately 40% and increase the risk of unplanned pregnancies in women with epilepsy. AEDs also increase the risk of birth defects in offspring of women with epilepsy. We performed a national survey to determine obstetricians' and neurologists' knowledge of OC and AED interactions and the risk of birth defects for women with epilepsy taking AEDs. We received responses to a mailed questionnaire from 160 of 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 4 publications
3
48
0
5
Order By: Relevance
“…Women with epilepsy are at risk for decreased reproductive function and unsuccessful pregnancy outcomes. Krauss reports that women have better access to the neurologist before pregnancy, less chance of interaction with a neurologist during pregnancy, and an insufficient and often erroneous body of educational advice given to them by obstetricians and neurologists (22). Considerable effort has been made in the past several years to disseminate information to consumers and professionals in order to improve women's health, fetal health, and successful deliveries of healthy neonates.…”
Section: Clinical Care Of Women With Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Women with epilepsy are at risk for decreased reproductive function and unsuccessful pregnancy outcomes. Krauss reports that women have better access to the neurologist before pregnancy, less chance of interaction with a neurologist during pregnancy, and an insufficient and often erroneous body of educational advice given to them by obstetricians and neurologists (22). Considerable effort has been made in the past several years to disseminate information to consumers and professionals in order to improve women's health, fetal health, and successful deliveries of healthy neonates.…”
Section: Clinical Care Of Women With Epilepsymentioning
confidence: 99%
“…Nonenzyme-inducing drugs (felbamate, lamotrigine, VPA, gabapentin, and vigabatrin) do not interfere with birth control pills (Table 6). Unfortunately, this information is not well known by general neurologists and even less well known by obstetricians (22). Simply increasing the estrogenic component to 50 pg or more may prevent contraceptive failure.…”
Section: Aed Effects On Steroid Metabolismmentioning
confidence: 99%
“…Estos hallazgos sugieren un conocimiento limitado por parte de los médicos de las interacciones entre la anticoncepción de tipo hormonal y los antiepilépticos, situación que se ha descrito en distintos estudios que evalúan los conocimientos que estos tienen de la epilepsia en la mujer, en especial cuando se valora minuciosamente dicha interacción (12,13). Este aspecto no fue evaluado en el presente estudio.…”
Section: Discussionunclassified
“…An early survey in the US suggested that medical practitioners had limited knowledge of interactions between contraception and AEDs in women with epilepsy [8]. In another US study, only 4% of neurologists and none of the obstetricians knew the effects of the six most common AEDs on OCs [9]. A survey published in 2005 showed that about 70% of primary care physicians recognized that certain AEDs might interfere with the efficacy of OCs [10].…”
Section: Discussionmentioning
confidence: 99%